T1ρ Hip Cartilage Mapping in Assessing Patients With Cam Morphology: How Can We Optimize the Regions of Interest?. Issue 4 (April 2017) - Anwander, Helen; Rakhra, Kawan S.; Melkus, Gerd; Beaulé, Paul E.
Abstract: Background: T1ρ MRI has been shown feasible to detect the biochemical status of hip cartilage, but various region‐of‐interest strategies have been used, compromising the reproducibility and comparability between different institutions and studies. Questions/purposes: The purposes of this study were (1) to determine representative regions of interest (ROIs) for cartilage T1ρ mapping in hips with a cam deformity; and (2) to assess intra‐ and interobserver reliability for cartilage T1ρ mapping in hips with a cam deformity. Methods: The local ethics committee approved this prospective study with written informed consent obtained. Between 2010 and 2013, in 54 hips (54 patients), T1ρ 1.5‐T MRI was performed. Thirty‐eight hips (38 patients; 89% male) with an average age of 35 ± 7.5 years (range, 23‐51 tears) were diagnosed with a cam deformity; 16 hips (16 patients; 87% male) with an average age of 34 ± 7 years (range, 23‐47 years) were included in the control group. Of the 38 patients with a cam deformity, 20 were pain‐free and 18 symptomatic patients underwent surgery after 6 months of failed nonsurgical management of antiinflammatories and physical therapy. Exclusion criteria were radiologic sings of osteoarthritis with Tönnis Grade 2 or higher as well as previous hip surgery. Three region‐of‐interest (ROI) selections were analyzed: Method 1: as a whole; Method 2: as 36 to 54 small ROIs (sections of 30° in the sagittal plane and 3 mm in the transverse plane); Method 3a: as six ROIs (sections of 90° in the sagittal plane and one‐third of the acetabular depth in the transverse plane: the anterosuperior and posterosuperior quadrants, divided into lateral, intermediate, and medial thirds); and Method 3b: as the ratio (anterosuperior over posterosuperior quadrant). ROIs in Method 3 represent the region of macroscopic cartilage damage, described in intraoperative findings. To asses interobserver reliability, 10 patients were analyzed by two observers (HA, GM). For intraobserver reliability, 20 hip MRIs were analyzed twice by one observer (HA). To assess interscan reliability, three patients underwent two scans within a time period of 2 weeks and were analyzed twice by one observer (HA). T1ρ values were compared using Student's t test. Interclass correlation coefficient (ICC) and root mean square coefficient of variation (RMS‐CV) were used to analyze intraobserver, interobserver, and interscan reliability. Results: Patients with a cam deformity showed increased T1ρ values in the whole hip cartilage (mean: 34.0 ± 3.8 ms versus 31.4 ± 3.0 ms; mean difference: 2.5; 95% confidence interval [CI], 4.7‐0.4; p = 0.019; Method 1), mainly anterolateral (2), in the lateral and medial thirds of the anterosuperior quadrant (mean: 32.3 ± 4.9 ms versus 29.4 ± 4.1 ms; mean difference: 3.0; 95% CI, 5.8‐0.2; p = 0.039 and mean 36.5 ± 5.6 ms versus 32.6 ± 3.8 ms; mean difference: 3.8; 95% CI, 6.9‐0.8; p = 0.014), and in the medial third of the posterosuperior quadrant (mean: 34.4 ± 5.5 ms versus 31.1 ± 3.9 ms; mean difference: 3.1; 95% CI, 6.2‐0.1; p = 0.039) (3a). The ratio was increased in the lateral third (mean: 1.00 ± 0.12 versus 0.90 ± 0.15; mean difference: 0.10; 95% CI, 0.18‐0.2; p = 0.018) (3b). ICC and RMS‐CV were 0.965 and 4% (intraobserver), 0.953 and 4% (interobserver), and 0.988 (all p < 0.001) and 9% (inter‐MR scan), respectively. Conclusions: Cartilage T1ρ MRI mapping in hips is feasible at 1.5 T with strong inter‐, intraobserver, and inter‐MR scan reliability. The six ROIs (Method 3) showed a difference of T1ρ values anterolateral quadrant, consistent with the dominant area of cartilage injury in cam femoroacetabular impingement, and antero‐ and posteromedial, indicating involvement of the entire hip cartilage health. The six ROIs (Method 3) have been shown feasible to assess cartilage damage in hips with a cam deformity using T1ρ MRI. We suggest applying this ROI selection for further studies using quantitative MRI for assessment of cartilage damage in hips with a cam deformity to achieve better comparability and reproducibility between different studies. The application of this ROI selection on hips with other deformities (eg, pincer deformity, developmental dysplasia of the hip, and acetabular retroversion) has to be analyzed and potentially adapted. Level of Evidence: Level III, diagnostic study.